2022
DOI: 10.1021/jacs.2c00465
|View full text |Cite
|
Sign up to set email alerts
|

Selective Photoelectrocatalytic Glycerol Oxidation to Dihydroxyacetone via Enhanced Middle Hydroxyl Adsorption over a Bi2O3-Incorporated Catalyst

Abstract: Photoelectrocatalytic (PEC) glycerol oxidation offers a sustainable approach to produce dihydroxyacetone (DHA) as a valuable chemical, which can find use in cosmetic, pharmaceutical industries, etc. However, it still suffers from the low selectivity (≤60%) that substantially limits the application. Here, we report the PEC oxidation of glycerol to DHA with a selectivity of 75.4% over a heterogeneous photoanode of Bi2O3 nanoparticles on TiO2 nanorod arrays (Bi2O3/TiO2). The selectivity of DHA can be maintained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 56 publications
3
105
1
Order By: Relevance
“…The PEC biosensor was fabricated on a TiO 2 NRs supporting photoelectrode (Figure a) using sequential in situ growth of Zr-MOF and loading of Cu­(II) ions. TiO 2 NRs on a fluorine-doped tin oxide (FTO) substrate were prepared via a hydrothermal method according to the reported literature, and their morphology was examined by scanning electron microscopy (SEM). The as-synthesized TiO 2 NRs revealed a nearly perpendicular nanorod array structure and a smooth wall (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The PEC biosensor was fabricated on a TiO 2 NRs supporting photoelectrode (Figure a) using sequential in situ growth of Zr-MOF and loading of Cu­(II) ions. TiO 2 NRs on a fluorine-doped tin oxide (FTO) substrate were prepared via a hydrothermal method according to the reported literature, and their morphology was examined by scanning electron microscopy (SEM). The as-synthesized TiO 2 NRs revealed a nearly perpendicular nanorod array structure and a smooth wall (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Methanol presents a more remarkable inhibition for CO evolution (Figure S21), indicating glycerol is directly oxidized by the holes instead of the * OH derived from water oxidation. [49][50][51] 3-Benzenepropanal was used as a probe molecule to investigate the decarbonylation process in acetonitrile/water solution. The CO evolution rate is the highest in pure acetonitrile and decreased with increasing water content, which further confirms photogenerated holes are responsive for the decarbonylation to CO (Figure S22).…”
Section: Methodsmentioning
confidence: 99%
“…Compared with biodiesel (an exemplary liquid fuel), glycerol enables a lowly added value, indicating that it necessitates a further chemical conversion. Generally, an accessible route, namely the conversion of glycerol to value‐added products, has been proposed 30,160,161 …”
Section: Pr Of Solid Waste To Value‐added Chemicals and H2 Fuelsmentioning
confidence: 99%
“…Generally, an accessible route, namely the conversion of glycerol to value-added products, has been proposed. 30,160,161 Most of current studies have been devoted to converting glycerol into hydrogen. 162 For example, Reddy et al 140 reported Ni(OH) 2 quantum dots decorated on TiO 2 nanotubes for hydrogen generation.…”
Section: Pr Of Lipidmentioning
confidence: 99%
See 1 more Smart Citation